Simplify 5 + 2{x - 4[3x + 7(2 - x)]}.

5 + 2{x - 4[3x + 7(2 - x)]} = 5 + 2{x - 4[3x + 14 - 7x]} = 5 + 2{x - 4[14 - 4x]} = 5 + 2{x - 56 + 16x} = 5 + 2{17x - 56} = 5 + 34x - 112 = 34x - 107

Question

Asked 11/5/2013 11:54:47 AM

Updated 3/5/2017 6:06:29 PM

1 Answer/Comment

Edited by Andrew. [3/3/2017 8:00:39 AM]

s

Rating

8

5 + 2{x - 4[3x + 7(2 - x)]}

= 5 + 2{x - 4[3x + 14 - 7x]}

= 5 + 2{x - 4[14 - 4x]}

= 5 + 2{x - 56 + 16x}

= 5 + 2{17x - 56}

= 5 + 34x - 112

= 34x - 107

= 5 + 2{x - 4[3x + 14 - 7x]}

= 5 + 2{x - 4[14 - 4x]}

= 5 + 2{x - 56 + 16x}

= 5 + 2{17x - 56}

= 5 + 34x - 112

= 34x - 107

Added 3/5/2017 6:06:29 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [3/6/2017 1:45:24 AM]

Simplify b(a + b) - a(a - b).
User: (y 3 - 125) ÷ (y - 5)
**Weegy:** 3-3 = 0 **User:** Simplify b(a + b) - a(a - b).
**User:** -2x(x 2 - 3)
**User:** The meteorologist says there's a cold front moving in. How will you prepare?
**Weegy:** Basically be prepared for rain, thunderstorms, and so on. **User:** Which of the following characteristics must an air mass have?
(More)

Question

Updated 5/24/2014 9:23:34 AM

3 Answers/Comments

b(a + b) - a(a - b)

= ab + b^2 - a^2 + ab

= 2ab + b^2 - a^2

= ab + b^2 - a^2 + ab

= 2ab + b^2 - a^2

Added 5/24/2014 9:21:17 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/24/2014 9:22:02 AM]

(y^3 - 125) ÷ (y - 5)

= (y - 5)(y^2 + 5y + 25)/(y - 5)

= y^2 + 5y + 25

= (y - 5)(y^2 + 5y + 25)/(y - 5)

= y^2 + 5y + 25

Added 5/24/2014 9:22:55 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/24/2014 9:24:55 AM]

Find the quotient.
48a^3bc^2 / 3abc
**Weegy:** 48a^3bc^2 / 3abc = 16a^2c (More)

Question

Updated 7/2/2014 9:51:04 AM

0 Answers/Comments

32,771,095

questions answered

There are no comments.